Techno economics involed with the on farm productation of pure Jersey embryos in Ooty, Nilgiris - PATEL, D V; DHANASEKARAN, N; INKHATE, R V; KUNJU, M; KASIRAJ, R (The Indian Journal of Animal Sciences, 2011)
With the present scenario of increased demand for exotic animals, Pure Jersey/HF bulls and nonavailability of desired genetics, there is a need to exploit the available gennplasm. Inview ofthis a collaborativeEmbryoTransfer (ET) work was taken up by SAGand NJF to superovulate and flush available elite females and then transfer embryos into the synchronized recipients available in the field. All donors and recipients selected were tested against TB, JD and Brucellosis. Disease free animals were selected and taken for programming. Total 6 Jersey cows were flushed using semen from the exotic bulls.Â· Total 49 embryos were recovered with an average of 8.17 embryos per flush, while viable embryo recovery was 32 with an average of 5.33 per flush. Nine fresh embryos were transferred in 8 recipients, while 2 frozen transfers were also done in 2recipients. The overall direct costinvolved including biologicals, consumables, administrative and TAJDAetc. was Rs 104773 with Rs 17462 per flush and Rs 3274 per viable embryo recovered. It was concluded that as cost to produce one pure bred viable embryo is Rs 3274, ETT should be used as a tool by established farms and institutions for producing elite gennplasm. Â